Aplikasi Penerjemah Bahasa Isyarat Indonesia Ke Dalam Huruf Abjad - Yunus, Mughaffir; anwar, yusril (Fakultas Teknik Universitas Muhammadiyah Parepare, 2022)
Sign language is the language used by people with limited speech or hearing. However, not everyone knows how to translate sign language in letters. Therefore, this research is motivated because there are many people who are normal or who do not have disabilities in speaking or listening who do not know how to communicate with people who have these limitations. So from this i raised a topic for the final project,